Structural progression rate decreases over time on serial radiography and magnetic resonance imaging of sacroiliac joints and spine in a five-year follow-up study of patients with ankylosing spondylitis treated with tumour necrosis factor inhibitor. (4th May 2019) - Pedersen, SJ; Weber, U; Said-Nahal, R; Sørensen, IJ; Loft, AG; Kollerup, G; Juul, L; Frandsen, PB; Thamsborg, G; Madsen, OR; Møller, J; Balding, L; et al.
Abstract : Objective : To investigate temporal changes in structural progression assessed by serial conventional radiography and magnetic resonance imaging (MRI) of the sacroiliac joints (SIJs) and spine in patients with ankylosing spondylitis (AS) treated with tumour necrosis factor (TNF) inhibitor for 5 years. Method : Forty-two patients were included and 33 patients were followed for 5 years in a prospective investigator-initiated study. Conventional radiographs were required four times and MRI seven times. The modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS); Spondyloarthritis Research Consortium of Canada (SPARCC) MRI SIJ and Spine Inflammation, and SPARCC MRI SIJ Structural Score (SSS) for Fat, Erosion, Backfill, and Ankylosis; and the Canada–Denmark MRI scores for Spine Inflammation, Fat, Erosion, and New Bone Formation (NBF) were applied. Results : Compared with baseline, MRI Inflammation had decreased significantly at week 22 (spine)/week 46 (SIJ) and thereafter. MRI SIJ Fat (from week 22), SIJ Ankylosis, Spine NBF, and mSASSS had increased significantly at week 46 and thereafter. SIJ Erosion had decreased from year 2. The annual progression rate in mSASSS was significantly higher during weeks 0–46 compared to week 46 to year 3. In multivariate regression analyses, baseline SIJ Inflammation and Backfill were independent predictors of 5 year progression in SIJ Ankylosis. Spine Erosion predicted progression in Spine NBF. Longitudinally, Ankylosing Spondylitis Disease Activity Score, Bath Ankylosing Spondylitis Disease Activity Index, MRI Spine Inflammation, Fat, and Erosion scores were significantly associated with mSASSS. SIJ Inflammation, Fat, Erosion, and Backfill scores were longitudinally associated with SIJ Ankylosis. Structural progression was not associated with body mass index, smoking, or Assessment of SpondyloArthritis international Society Non-Steroidal Anti-Inflammatory Drug Index. Conclusion : In a 5 year follow-up study of patients with AS treated with TNF inhibitor, structural progression decreased over time.